FACTORS IDENTIFICATION FOR STRATEGIC FINANCIAL MANAGEMENT OF AN EFFECTIVE ROAD MAINTENANCE: A REVIEW (ASEAN Engineering Journal, 2025)
Road maintenance works need to be carried out regularly to maintain pavement conditions and ensure road user safety. However, road maintenance management is becoming more complex due to large numbers of ageing roads and limited funds for maintenance. Finance is among the crucial components of road maintenance operations. Ineffective financial management leads to the inefficient use of funds and delay of maintenance work. It has been demonstrated that strategic management practices have contributed to increasing the effectiveness of financial management due to the practices that centre on methods towards achieving maintenance goals. Therefore, this paper conducts a review to identify the financial management factors that will impact the effectiveness of road maintenance financial management. Data were sourced from electronic databases with specific searched keywords related to financial management. Factor searching focused on prevalent domains such as financial goals, financial planning, financial organizing, financial leading, and financial monitoring. A total of seventy-two (72) papers have undergone review, unveiling fifty-two (52) distinct factors. Financial goals contribute about seven (7) factors, financial planning to twenty-one (21) factors, financial organizing about seven (7) factors, financial leading to nine (9) factors, and financial monitoring to eight (8) factors. The review conducted in this paper sheds light on the multitude of factors influencing financial management effectiveness in road maintenance. Identifying key areas can develop targeted strategies to enhance financial efficiency and optimize maintenance efforts. The findings also underscore the necessity for continued research in this field to address the complexities of road maintenance and ensure the long-term sustainability of transportation infrastructure.